Transcriptomic classes of BCR-ABL1 lymphoblastic leukemia - Kim, Jaeseung C.; Chan-Seng-Yue, Michelle; Ge, Sabrina; Zeng, Andy G. X.; Ng, Karen; Gan, Olga I.; Garcia-Prat, Laura; Flores-Figueroa, Eugenia; Woo, Tristan; Zhang, Amy Xin Wei; Arruda, Andrea; Chithambaram, Shivapriya; et al. (Nature genetics, 2023)
In BCR-ABL1 lymphoblastic leukemia, treatment heterogeneity to tyrosine kinase inhibitors (TKIs), especially in the absence of kinase domain mutations in BCR-ABL1 , is poorly understood. Through deep molecular profiling, we uncovered three transcriptomic subtypes of BCR-ABL1 lymphoblastic leukemia, each representing a maturation arrest at a stage of B-cell progenitor differentiation. An earlier arrest was associated with lineage promiscuity, treatment refractoriness and poor patient outcomes. A later arrest was associated with lineage fidelity, durable leukemia remissions and improved patient outcomes. Each maturation arrest was marked by specific genomic events that control different transition points in B-cell development. Interestingly, these events were absent in BCR-ABL1 + preleukemic stem cells isolated from patients regardless of subtype, which supports that transcriptomic phenotypes are determined downstream of the leukemia-initialing event. Overall, our data indicate that treatment response and TKI efficacy are unexpected outcomes of the differentiation stage at which this leukemia transforms. Transcriptomic analysis of BCR-ABL1 lymphoblastic leukemia identifies three subgroups, each associated with a maturation arrest at a specific stage of B-cell progenitor differentiation and distinct genetic and clinical features.